Dampak Perkembangan Urbanisasi Terhadap Tingkat Pertumbuhan Penduduk Di Perkotaan - M. Ridwan Said Ahmad; Watif Massuanna Massuanna; Muh Falak Cahyadi; Syarifah Aini Aini; Sri Rahmi Rahmi (Ridwan Institute, 2022)
The main objective in the discussion of this material is to determine the impact of urbanization development on the growth rate of people in urban areas. Urbanization that occurs in people's lives does not just happen, but through various processes and encouragement from various conditions that arise in society. Research or observations related to the impact of urbanization development on the growth rate of people in urban areas will provide an overview of the conditions that occur in urban communities with the various phenomena it causes. Urbanization is one of the processes of social change that occurs rapidly among changes that occur throughout the world. Urbanization can simply be understood as a form of movement of people from rural areas to cities. There are many positive and negative impacts caused by urbanization on urban population growth. In this study used descriptive qualitative method, namely, by observing directly the phenomena that occur in urban areas.